Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-02-14T20:53:05+01:00
( x + 2y = - 2
( 2x - y = 1

( x = - 2y - 2
( 2*(- 2y - 2) - y = 1

( x = - 2y - 2
( - 4y - 4 - y = 1

( x = - 2y - 2
( - 4y - y = 1 + 4

( x = - 2y - 2
( - 5y = 5 /:(- 5)

( x = - 2y - 2
( y = - 1

( x = - 2*(-1) - 2
( y = - 1

( x = 2 - 2
( y = - 1

( x = 0
( y = - 1


  • Użytkownik Zadane
2010-02-14T21:01:13+01:00
X+2y=-2/*2
2x-y=1

2x+4y=-4
2x-y=1

5y=-5/:5
y=-1

2x-y=1
2x+1=1
2x=1-1
x=0

odp: x=0, y=-1
2010-02-14T23:19:54+01:00
X+2y= -2
2x-y=1

x=-2-2y
2(-2-2y)-y=1
-4-4y-y=1
-5y=5
y=-1

x=-2-2*(-1)
x=-2+2
x=0